2018
DOI: 10.3390/en11102645
|View full text |Cite
|
Sign up to set email alerts
|

A Shape Optimization Method of a Specified Point Absorber Wave Energy Converter for the South China Sea

Abstract: In this paper, a shape optimization method of a truncated conical point absorber wave energy converter is proposed. This method converts the wave energy absorption efficiency into the matching problem between the wave spectrum of the South China Sea and the buoy’s absorption power spectrum. An objective function which combines these two spectra is established to reflect the energy absorbing efficiency. By applying Taguchi design, the frequency domain hydrodynamic analysis and the response surface method (RSM),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Therefore, the damping coefficient (RPTO) and the stiffness coefficient (XPTO) of the permanent magnet synchronous motor need be controlled. According to Equations (6), (7) and (18), the following conditions should be met as, ( )…”
Section: Letmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the damping coefficient (RPTO) and the stiffness coefficient (XPTO) of the permanent magnet synchronous motor need be controlled. According to Equations (6), (7) and (18), the following conditions should be met as, ( )…”
Section: Letmentioning
confidence: 99%
“…In addition, ocean wave energy has a quite higher energy density than solar energy and is more stable than wind energy [2][3][4]. Up to date, several wave energy converters (WEC) concepts have been studied, and the research focuses so far mainly on the mechanical structure, the hydrodynamic aspect and the energy conversion rate of different WECs [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the actuator efficiency had a major effect on the absorbed power and control performance, especially when reactive control is applied, as it depends on the actuator. Wen, et al [70] utilized Taguchi method and an objective function in order to optimize the shape and dimensions of a conical floater to maximize the power harvesting efficiency for the coast of China.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…This is because the costs involved in producing energy using ocean waves are currently much higher than those for other renewables [6]. Therefore, in the last decade, a large number of investigations have been carried out to optimise wave energy converter (WEC) design and dimensions [7][8][9][10][11][12], power generation settings (PTO) [13,14], and the position of WECs in a wave farm [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%